ANALISIS HUBUNGAN FAKTOR INDIVIDU DAN BEBAN KERJA MENTAL DENGAN STRES KERJA - Intan Sulistyana Mustika Suci (Universitas Airlangga, 2018)
Stress is the stimulation of the situation which could threaten the physical and psychological that cannot be tolerated by an individual because of limited ability. The general objective of this research is to analyze the individual factors and mental workload with stress. The research was done in observational. Population in this study are all the workers are there in packer PT. X amount of 10 workers and analysis of the data used is the spearman correlation test to known the correlation between education and mental workload with job stress, pearson correlation test to known the correlation between age and work period with job stress and contingency test to known the correlation between marital status with job stress. Based on the results of the statistical tests, a variable that has a strong relationship with stress is mental work load variable (0.667), while variables that have a relationship with stress is the level of education (-0.102), marital status (0.378),the period of employment (-0.102) and age (-0.408). From the results of this research it can be concluded that the majority of respondents in the age range 21–40 years (60%) and has a working time of 5–9 years (70%) by level of education finished high school (60%) and be married (60%). The relationship between mental workload with the stress of having strong correlation.Keywords: job stress, mental workload